Endothelin-1 gene polymorphism in patients with malignant arrhythmias - Kozák, Milan; Izakovičová Hollá, Lydie; Křivan, Lubomír; Vašků, Anna; Sepši, Milan; Semrád, Bořivoj; Vácha, Jiří (Journal of cardiovascular pharmacology, 2004)
The endothelins are peptides with vasoconstricting and growth-promoting properties. Endothelin-1 (ET-1) is known with its direct positive inotropic and chronotropic effects on isolated heart and with growth effects. The aim of this pilot study was to investigate the frequency distribution of the common polymorphism of the ET-1 gene and its possible relation with hemodynamic consequences of malignant ventricular arrhythmias in patients with structural heart disease. We studied 26 consecutive patients with malignant ventricular arrhythmias and implantable cardioverterdefibrillators with a mean age of 62.7 +/- 12.2 years and a mean left ventricular ejection fraction of 0.37 +/- 11.0. Taq polymorphism of ET-1 was detected using our original polymerase chain reaction method. The polymerase chain reaction product with a length of 358 basepairs (bp) (primers 5'-CAA ACC GAT GTC CTC TGT A-3' and 5'-ACC AAA CAC ATT TCC CTA TT-3') in its non-mutated form contains a target sequence for TaqI restrictive enzyme, while a mutated product loses this cleavage site. Of 26 patients, nine (34%) had recurrent palpitations and eight (30.8%) had syncopes during their malignant arrhythmias. Nineteen patients were given amiodarone after implantable cardioverter-defibrillator insertion and seven were not treated with amiodarone. Fifteen patients had (++), 11 (+-) and 0 (- -) ET-1 genotype. The risk for syncopes was associated with the (++) genotype of the ET-1 gene (P = 0.01). Patients receiving amiodarone had significantly higher frequency of the (++) genotype (P = 0.011). All our results indicate that the presence of the ET-1 genotype (++) in patients with structural heart disease, severe left ventricular dysfunction and malignant ventricular arrhythmias increases the risk for these patients of hemodynamic collapse during these arrhythmias.
Keywords: Stroke Volume; Recurrence; amiodaron; antiarytmika; Female; Phenotype; výsledek terapie; ženské pohlaví; sekvence aminokyselin; Hemodynamics; hemodynamika; časové faktory; funkce levé komory srdeční; Time Factors; Gene Frequency; lidé; synkopa; Molecular Sequence Data; Ventricular Function, Left; Pilot Projects; recidiva; Syncope; pilotní projekty; genetická predispozice k nemoci; Amino Acid Sequence; Treatment Outcome; Genetic Predisposition to Disease; Arrhythmias, Cardiac; frekvence genu; Risk Factors; molekulární sekvence - údaje; Male; Aged; tepový objem; polymorfismus genetický; rizikové faktory; endotelin-1; Defibrillators, Implantable; lidé středního věku; Endothelin-1; senioři; mužské pohlaví; fenotyp; defibrilátory implantabilní; Anti-Arrhythmia Agents; Polymorphism, Genetic; Middle Aged; srdeční arytmie; Amiodarone; Humans